Histoire Croisée - Bénédicte Zimmermann (Footprint)
Globalization makes understanding worldmaking processes a crucial issue. During the Cold War the social sciences mainly addressed this issue through comparative studies which mirrored the logic of the world-historical confrontation. In this respect 1989 fostered not only a political turn but an epistemological one. The new political situation fueled the development of approaches dedicated to the study of relations and interdependencies between different parts of the world.